EQUIPMENT ANAEROBIC DIGESTION OF SEWAGE SLUDGE FROM METOYUOTRYMANNYA AND BIOGAS UTILIZATION IN COMMUNAL SEWAGE TREATMENT FACILITIES - , С. Б., К. Б. (Municipal economy of cities. Series: «Economy science», 2013)
The analysis of the main factors, parameters and characteristics of equipment stores anaerobic digestion of sewage sludge that affect the stability of the formation of biogas